DEAF STUDENTS’ ABILITIES IN ENGLISH VOCABULARY AT SPECIAL SCHOOL - Rika Wahyuni Tambunan (Journal of Language, Literature and Teaching, 2022)
Deaf students are included in students with special needs because it is a type of physical disability. In teaching, teachers are faced with various challenges. For this reason, special methods are needed in teaching so that learning becomes effective. The support and participation of the school are also needed. English lessons in public schools find many difficulties, especially in schools with special needs. This study aims to describe the teacher's strategy in teaching English to deaf students at SLB C Muzdalifah. This research used a qualitative method. Data collection techniques used are observation, interviews, and documentation (pictures). To analyze the data obtained, the authors use data collection techniques, data reduction, data display, and drawing conclusions. The results of this study indicate that the teacher applies a learning strategy that contains repeating material and periodically checking students' understanding. However, in practice, it is still less effective. The sitting position of students in the classroom is also arranged before the lesson begins. Total Physical Response and Grammar Translation Methods are used as a strategy for developing English vocabulary for deaf students combined with sign language. However, even though the teaching is still not effective, in general, it can be concluded that the objectives of teaching English using this strategy can be achieved. Teaching English to deaf students at SLB C Muzdalifah is focused on reading and speaking skillsKeywords: deaf students, English vocabulary, special school